The Timing of Antidepressant Effects: A Comparison of Diverse Pharmacological and Somatic Treatments - Carlos A. Zarate Jr; Giacomo Salvadore; Ioline D. Henter; David Latov; Cristina Wheeler-Castillo; Jacqueline Baumann; Rodrigo Machado-Vieira (MDPI AG, 2010)
Currently available antidepressants used to treat major depressive disorder (MDD) unfortunately often take weeks to months to achieve their full effects, commonly resulting in considerable morbidity and increased risk for suicidal behavior. Our lack of understanding of the precise cellular underpinnings of this illness and of the mechanism of action of existing effective pharmacological treatments is a large part of the reason that therapies with a more rapid onset of antidepressant action (ROAA) have not been developed. Other issues that need to be addressed include heterogeneous clinical concepts and statistical models to measure rapid antidepressant effects. This review describes the timing of onset of antidepressant effects for various therapies used to treat MDD. While several agents produce earlier improvement of depressive symptoms (defined as occurring within one week), the response rate associated with such agents can be quite variable. These agents include both currently available antidepressants as well as other pharmacological and non-pharmacological interventions. Considerably fewer treatments are associated with ROAA, defined as occurring within several hours or one day. Treatment strategies for MDD whose sustained antidepressant effects manifest within hours or even a few days would have an enormous impact on public health.